Overview on the target population and methods used in care pathway projects: A narrative review. Issue 10 (7th July 2021) - Seys, Deborah; Coeckelberghs, Ellen; Sermeus, Walter; Van Zelm, Ruben; Panella, Massimiliano; Babu Payedimarri, Anil; Vanhaecht, Kris
Abstract: Background: There is evidence that the efficiency and effectiveness of care processes can be improved in all countries. Care pathways (CPs) are proposed as a method to improve the quality of care by reducing variation. During the last decades, CPs have been intensively used in practice. The objective of this study is to examine the study designs for investigating CPs, for which pathologies CPs are used and what the reported indicators to measure the impact of CPs are. Methods: A narrative review of the literature published from 2015 to 2019 was performed. Results: We identified 286 studies, of which 207 evaluated the impact of CPs, 33 were review articles, 29 studies described the development of a CP, 12 were study protocols and 5 opinion papers. The most frequently reported study design for studying the impact of a CP is pre‐posttest (n = 82), followed by cross‐sectional studies (n = 50). Oncology, cardiovascular disease and abdominal surgery are the domains with the highest numbers of studies evaluating the impact of CPs. Financial (n = 86), process (n = 76) and clinical indicators (n = 74) are the most frequently reported indicators while service (n = 12) and team indicators (n = 6) are less reported. Conclusions: Based on the relative low number of identified studies compared with the number of CP projects in organisations, we conclude that the CP knowledge is not only found in the literature. We, therefore, argue that (inter)national scientific societies should not only focus on searching and spreading evidence on the content of care but also enhance their knowledge sharing initiatives on the organisation of care processes.